Analisis Kesulitan Belajar Matematika dalam Menyelesaikan Soal Cerita Peserta Didik Kelas 1 - Kurnia Ully Wardani; Siti Rahayu; Lovika Ardana Riswari (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to determine the learning difficulties of students in terms of solving story problems in the mathematics subject of Addition material. This research was conducted at SD N Pati Wetan 01 with a total of 5 students. The type of research used is descriptive qualitative. While the source of data obtained using interviews, observations, documentation in the form of student answers. Newman's theory is used as a reference in the analysis of learners' learning difficulties. The result of the study was that all five subjects experienced some difficulties. like; 1) AZ has learning difficulties in the form of a lack of understanding of the content of the reading in the form of stories; 2) MF has a dislike of mathematics learning; 3) AR has difficulty solving story problems in terms of finding formulas and studying story problems; 4) NB has a lack of understanding in the content of the story problem and is able to solve the problem but the answer is not right; and AH has difficulty yet understanding the addition operation. Some difficulties are concluded to be a lack of understanding of the construction of mathematical models, a lack of understanding of addition operations, and a lack of precise answers from learners.